PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN METAKOGNITIF BERBASIS HUMANISTIK UNTUK MENUMBUHKAN BERPIKIR KRITIS SISWA PADA MATERI HIMPUNAN KELAS VII (JPP, 2011)
This study aim to know whether the learning devices of mathematics by using Humanistic Based Metacognitive Approach to grow Critical Thinking Ability on Set Material. The type of this study is development research using modified Thiagarajan, Semmel Semmel model. The learning devices that developed are syllabus, lesson plan, student book, worksheet, and the Critical Thinking Ability Test. The results suggests that obtained learning devices of syllabus with a mean value 3.67, lesson plan with a mean value 3.79, student books with a mean value 3.67, worksheet with a mean value 3.70, and critical thinking ability test with a mean value 3.76, then the learning devices are valid. The process of mathematics learning by using humanistic based metacognitive approach to grow critical thinking ability is proven to be effective. The effectiveness is characterized by the achievement of student mastering learning criteria is more than orequal to 80% classically and is greater than or equal to 65 individually, the critical thinking abilitiy of students are affected both by the activitiy and skills of students by 89.8 % and the average of critical thinking skills in class of test device is better than the control class.Keywords: Development of Learning Devices, Metacognitive Approach, humanistic, Critical Thinking.